THE STUDY SYSTEM IN MADRASAH‘S DURING THE PERIOD OF THE GREAT SELJUKS (1038-1157) AND THE ACTIVITY OF MADRASAH MUDARRIS‘S - Rajapov Pirnazar Sardor ogli (Journal Park Publishing, 2024)
This article analyzes the reforms which carried out in the field of study in the Great Seljuk Sultanate and the reasons for them. Also, it is highlighted that the process of establishing madrasahs in Khorasan, Kerman, Iraq, Syria and Anatolia regions of the country and the study system in these madrasahs. In particular, subjects and educational references in the curriculum of madrasahs were also discussed. In addition to, the role of madrasah mudarris‘s such as Abulma’ali Juwayni (419/1028-478/1085), Imam Ghazali (450/1058-505/1111), Abu Is’haq Shirazi (393/1003-476/1083) and others have been revealed, who activated at the Seljuki society during the period of XIth century.
Keywords: The Great Seljuk Sultanate, madrasah, study system, Sultan Alp Arslan, Sultan Malik-Shah, Nizamiya madrasah of Baghdad, mudarris, muid, Abulma’ali Juwayni, Imam Ghazali, Abu Is’haq Shirazi.